3-(1H-Tetrazol-5-yl)pyridinium chloride - Jing Dai; Miao-Jia Yu (Acta Crystallographica Section E, 2009)
In the cation of the title compound, C6H6N5+·Cl−, the pyridinium and tetrazole rings are nearly coplanar, making a dihedral angle of 5.05 (12)°. The cations and anions are connected by intermolecular N—H...Cl hydrogen bonds, forming a centrosymmetric [2 + 2] aggregate. The aggregates are stacked along the a axis.